Domain imaging in FINEMET ribbons - Silveyra, Josefina María (2010)
The magnetization behaviour of a ferromagnetic material depends on its domain structure, which in turn is largely determined by magnetic anisotropies. In this work, domain patterns were observed by a quite forgotten but still the simplest and the cheapest technique: the Bitter method. A systematic study of the evolution of the domain structure in FINEMET ribbons after thermal annealing is presented, correlating the results with the crystalline structure, magnetostriction and coercivity measurements.